Understanding the emotional impact of bowel cancer on younger patients: A mixed-method study of online narratives written by Australian young patients - Nissen, Vanda; Khalaj, Nafiseh; Olsson, Maja M.; Kalmaz, Kate; Meuter, Renata F. (Qualitative Health Communication, 2026)
Background: The incidence of bowel cancer in young people is rising globally. In response, many patients share their cancer journeys online to raise awareness. Aim: This study explores personal narratives of young bowel cancer patients and examines how cancer shaped their emotions. Method: We conducted a convergent mixed-methods study of narratives from Bowel Cancer Australia’s Never2Young webpage (N=48; age range: 21–48 years). Sentiment analysis quantified emotion distributions and valence across pre-diagnosis, diagnosis, and post-diagnosis. Thematic analysis was used to interpret these patterns. Results: Fear, sadness, and trust were most common. Overall sentiment was slightly positive. Women contributed longer narratives and showed marginally more negative valence than men. Temporal tokens were salient. Qualitative findings connected peaks in fear and sadness to uncertainty, age-related dismissal, and long waits for colonoscopy. Clearer information, family involvement, and self-care accompanied later increases in trust. Together, findings identify time (e.g., waiting for investigation) as a central mechanism linking care processes to emotion. Discussion: Emotional trajectories were phase-specific, with fear and sadness highest before diagnosis and trust increasing afterwards, often alongside persisting negative affect. Conclusion: Results of sentiment and thematic analysis of emotions reflect early delays/uncertainty and later clarity and support in young bowel cancer patients.